Nitric Oxide Dismutase (nod) Genes as a Functional Marker for the Diversity and Phylogeny of Methane-Driven Oxygenic Denitrifiers - Zhu, Baoli; Wang, Jiaqi; Bradford, Lauren M.; Ettwig, Katharina; Hu, Baolan; Lueders, Tillmann (Frontiers in Microbiology, 2019)
Oxygenic denitrification represents a new route in reductive nitrogen turnover which differs from canonical denitrification in how nitric oxide (NO) is transformed into dinitrogen gas. Instead of NO reduction via N2O to N2, NO is proposed to be directly disproportionated into N2 and O2 in oxygenic denitrification, catalyzed by the putative NO dismutase (Nod). Although a high diversity of nod genes has been recovered from various environments, still little is known about the niche partitioning and ecophysiology of oxygenic denitrifiers. One constraint is that nod as a functional marker for oxygenic denitrifiers is not well established. To address this issue, we compared the diversity and phylogeny of nod, 16S rRNA and pmoA gene sequences of four NC10 enrichments that are capable of methane-driven oxygenic denitrification and one environmental sample. The phylogenies of nod, 16S rRNA and pmoA genes of these cultures were generally congruent. And in each sample, the NC10 bacteria diversity inferred from different genes was also similar. A new set of NC10-specific nod primers was developed and used in qPCR. The abundance of NC10 bacteria inferred from nod genes was constantly lower than via 16S rRNA genes, but the difference was within one order of magnitude. These results suggest that nod is a suitable molecular marker for studying the diversity and phylogeny of methane-driven oxygenic denitrifiers, the further investigation of which may be of value to develop enhanced strategies for sustainable nitrogen or methane removal.